Opinions of Brazilian resuscitation instructors regarding resuscitation in the delivery room of extremely preterm newborns - Cristiane Ribeiro Ambrósio; Maria Fernanda Branco de Almeida; Ruth Guinsburg (Brazilian Society of Pediatrics, 2016)
Objective: To describe the opinions of pediatricians who teach resuscitation in Brazil on initiating and limiting the delivery room resuscitation of extremely preterm infants. Method: Cross‐sectional study with electronic questionnaire (Dec/2011-Sep/2013) sent to pediatricians who are instructors of the Neonatal Resuscitation Program of the Brazilian Society of Pediatrics, containing three hypothetical clinical cases: (1) decision to start the delivery room resuscitation; (2) limitation of neonatal intensive care after delivery room resuscitation; (3) limitation of advanced resuscitation in the delivery room. For each case, it was requested that the instructor indicate the best management for each gestational age between 23 and 26 weeks. A descriptive analysis was performed. Results: 560 (82%) instructors agreed to participate. Only 9% of the instructors reported the existence of written guidelines at their hospital regarding limitations of delivery room resuscitation. At 23 weeks, 50% of the instructors would initiate delivery room resuscitation procedures. At 26 weeks, 2% would decide based on birth weight and/or presence of fused eyelids. Among the participants, 38% would re‐evaluate their delivery room decision and limit the care for 23‐week neonates in the neonatal intensive care unit. As for advanced resuscitation, 45% and 4% of the respondents, at 23 and 26 weeks, respectively, would not apply chest compressions and/or medications. Conclusion: Difficulty can be observed regarding the decision to not resuscitate a preterm infant with 23 weeks of gestational age. At the same time, a small percentage of pediatricians would not resuscitate neonates of unquestionable viability at 26 weeks of gestational age in the delivery room.